Applications liposome in cancer drug delivery and treatment: A review - Pathak, Dr.Nandish; Pathak, Dr. Pratim (Asian Journal of Pharmaceutical Research and Development, 2019)
In the world the biggest challenges to cure the cancer because of the abnormal cancer cells growth in the human body which is near to uncontrollable. These cells known as the malignant cell because it produced the cancer. There are several treatments for cancer such as surgery, chemotherapy, radiation treatment etc. however such treatments have major side effects like normal cell got killed, loss of hair, the surgery person skill also in consideration and high chances of reoccurrences. Due to such side effects these treatment drugs are less popular. To reduces such side effects the liposomal based treatments are the most preferable solution. The liposomes are the phospholipid bilayer vesicles and it has high encapsulation capacity. Therefore, liposomal based treatment plays significant role in the cancer treatment with less toxicity and other many advantages. The liposomal based drug pegylated liposomal doxorubicin and daunorubicin have advanced effect in the body. Furthermore, the development of the liposomes as immunoliposomes, ligand targeted and molecular targeting. This review explores the liposomal based drug delivery system, its advance effect on the cancer cells and clinically approve liposomes formulations.